Financial Literacy and Love of Money Attitude toward Financial Management - Dewi Fadila; Yesita Astarina; Dwi Riana; Septini Kumalaputri; Melisa Kurnia Asfitri (Asean International Journal of Business, 2023)
Purpose – This study aims to determine the effect of financial literacy and attitudes love of money to financial management based on economic entity concept in UKM IKM Nusantara, Palembang City.Methodology/approach – This research is quantitative descriptive. The population in this study were 300 SMEs (Small Medium Enterprise) that are members of UKM IKM Nusantara. The sampling technique used is method purposive sampling and the criteria used in the study were SMEs that had joined as members of UKM IKM Nusantara for at least 3 years. The samples obtained in this study were 50 SMEs. This study uses primary data with data collection techniques using interviews, online questionnaires and observation.Findings – The results of this study indicate that as many as 84% of business actors in UKM IKM Nusantara who manage their finances have not implemented it economic entity concept. Furthermore, financial literacy has a significant positive effect on based financial management economic entity concept, where as love of money attitude does not affect the financial management based economic entity concept. Novelty/value – These findings indicate that SMEs need to have knowledge of financial management, especially based economic entity concept. This concept is a good financial management concept for SMEs to implement, especially in an effort to improve the best financial performance for SMEs.